Accounting Ethics in Financial Reporting in The Context of The Metaphor of ‘Lawang Sewu’ (thousands of doors, thousands of information, thousands of interests) - Debi Setyawati; Erina Sudaryati (The Indonesian Accounting Review, 2021)
This study aims to improve the readability and understanding of financial statements through a conceptual framework of financial reporting and its derivatives. This study employed an analytical method as a conceptual framework, where financial accounting standards, financial reporting, and the results are described by the term "Lawang Sewu" as a reflection. The results show that the term 'Lawang Sewu' has similarities with accounting ethics in financial reporting, where "lawang" (Javanese) means door refers to "door of information" and "sewu" (Javanese) means a thousand or many refers to having many information and interest in accounting reporting performance. Accounting ethics in financial reporting also describes the strength of the 'Lawang Sewu' building which is not damaged despite its old age. Financial statements reflect the company's past, present and future values. Based on the conceptual framework of accounting, financial statements must meet two qualitative criteria: primary qualitative (relevant and in accordance with actual conditions) and secondary qualitative (comparable, testable, timely and understandable). Thus, financial reports are expected to be transparent so that users can use them appropriately.